2020
DOI: 10.1073/pnas.1918387117
|View full text |Cite
|
Sign up to set email alerts
|

Defining how multiple lipid species interact with inward rectifier potassium (Kir2) channels

Abstract: Protein–lipid interactions are a key element of the function of many integral membrane proteins. These potential interactions should be considered alongside the complexity and diversity of membrane lipid composition. Inward rectifier potassium channel (Kir) Kir2.2 has multiple interactions with plasma membrane lipids: Phosphatidylinositol (4, 5)-bisphosphate (PIP2) activates the channel; a secondary anionic lipid site has been identified, which augments the activation by PIP2; and cholesterol inhibits the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
122
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(132 citation statements)
references
References 84 publications
10
122
0
Order By: Relevance
“…A number of simulation studies using the MARTINI force field have provided valuable insights into the association of membrane proteins 28,32,[49][50][51][52][53] and into protein-lipid interactions [54][55][56] . However, the current MARTINI model may also have some limitations 57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of simulation studies using the MARTINI force field have provided valuable insights into the association of membrane proteins 28,32,[49][50][51][52][53] and into protein-lipid interactions [54][55][56] . However, the current MARTINI model may also have some limitations 57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that crosstalk between different anionic lipids can affect the affinities of each lipid for the Kir2.2 channel 28 . Here, we show that the presence of 10% anionic lipid (POPS) in the lower leaflet of the bilayer does not affect the overall ΔΔG for PIP2 binding to Kir6.2 (Supplementary Figure 7).…”
Section: Step-wise Perturbation Of the Pip Molecule Bound To The Hkirmentioning
confidence: 99%
“…Cholesterol binding sites on membrane proteins were initially characterized using a variety of techniques, including electron spin resonance, photoaffinity labeling, molecular modeling and site-directed mutagenesis, which led to the identification of amino acid recognition motifs 15,37,[51][52][53][54] . CRAC (Cholesterol Recognition/interaction Amino acid Consensus) is characterized by the amino acid sequence (L/V)-X 1-5 -(Y)-X 1-5 -(K/R) 55 , while CARC is oriented in the opposite 56 .…”
Section: Cholesterol Binding Sites On Membrane Proteinsmentioning
confidence: 99%
“…Docking studies and MD simulations identified putative cholesterol binding sites in GIRK channels that involved various amino acid residues 14,28,37 . In particular, two sites are very similar to the positions observed in the cryoEM structure (CHS1 and CHS2).…”
Section: Cholesterol Binding Sites On Membrane Proteinsmentioning
confidence: 99%
See 1 more Smart Citation